The Development Model for Servant Leadership of Teacher Under The Primary Educational Service Area Office in Roi-Kean-Sara-Sin Province: The Development Model for Servant Leadership of Teacher Under The Primary Educational Service Area Office in Roi-Kean-Sara-Sin Province - Plomdongloy, Kasinphot; Duangchatom, Kritkanok; Ruangsuwan, Chayakan (RATANABUTH JOURNAL, 2024)
The purposes of this research were 1) to study the components and indicators of servant leadership of teacher. 2) to study the current situation, desirable condition and needs assessment of servant leadership of teacher under the primary educational service area office in Roi-Kean-Sara-Sin province. 3) create a model developing for servant leadership of teacher under the primary educational service area office in Roi-Kean-Sara-Sin province. 4) to study the results of using the model developing for servant leadership of teacher under the primary educational service area office in Roi-Kean-Sara-Sin province. The key informant group was 7 experts to confirm the components and indicators, 9 experts to draft model, 9 experts to confirm model and target groups were 15 teachers for study the results of using the model developing. The sample group consisted of 379 school administrators and teachers. The research tool was a interview form and questionnaire. Data were analyzed by means and standard deviation The research results found that: 1. The components and indicators of servant leadership of teacher, consisted of 5 components, Include 1) Building community 2) Value people 3) Commitment to the growth of people 4) Develop people 5) Building trust. 2. The overall current condition is at a high average level. The overall desirable condition was at the highest mean level. The Needs assessment was ranked from highest to lowest as follows: 1) Building trust 2) Value people 3) Commitment to the growth of people 4) Building community 5) Develop people.3. The model consists of components : 1) principles, 2) objectives, 3) content, 4) development process, and 5) measurement and evaluation. The model has a suitability assessment result. possibility and the overall usefulness of the model was at the highest level. 4. Results of the study using the model overall, the indicators were followed at the highest level. The results of the satisfaction assessment, the overall use of the model, satisfaction was at the highest level.